A Study on Modals Used in Text Your Say of The Jakarta Post - Widyanti, Elisabeth Rosalia; Yulia, Made Frida (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2013)
Communication happens not only in spoken form, but also in written form.Newspaper, as one form of written communication, provides ways for people to show theiropinion, intention, and thought. In the way people communicate by using language,modalsenable people to show something which is not simply positive or negative and each modal hassome functions to show peoples thought, intentions, or opinion.This study dealt with how modals were used by the commentators in Text Your Sayof The Jakarta Post. To solve the problem, the theories from Azar and Hagen (2009) andLeech and Svartvik (1994) were employed.The findings showed that there were 225 modalsfound in Text Your Say of The Jakarta Post issued in November 2012. They consisted ofmay, might, should, had better, be supposed to, must, have to, will, can, could, be able to, andwould. They were used by the commentators to show some functions. The functions were toshow 50% or less certainty, 90% certainty, 95% certainty, 100% certainty, ability/possibility,past ability, impossibility, necessity, strong necessity, advisability, suggestion, prohibition,expectation, unfulfilled wish/hypothesis, willingness, polite for want, and fulfilled futurecondition in the past.